Isolation and characterization of adhesive protein from green mussel (perna viridis) - Syed Muhammad, Syed Annuar Fauad (Universiti Teknologi Malaysia, 2000)
Mussel ejaculate threads from phenol gland which is situated at its leg area. These threads are built from adhesive protein, which contain amino aromatic L-dihydroxyphenylalanine (L-DOPA) acid. The objective of this study is to isolate and characterize adhesive protein from green mussel (perna veridis). First stage of the experiment is to isolate the protein from mussel feet by extraction method by using nitrogen liquid and dissolved in 0.7% perchloric acid followed by sulfuric acid and acetone. Second stage is to purify the protein using Sephadex Gel (G-200) and finally the characterization and identification by using HPLC, TLC, and electrophoresis gel. The protein concentrations after purification were measured using spectrophotometer with wave length 260 nm. Results for the three highest OD value samples showed that L-DOPA has been detected in the samples at Rf 0.15, 0.21, and 0.10. Results from HPLC showed that there are two types of amino acids contained in the samples. The first peak represents alanine while the second peak represents L-DOPA. From the samples amount of 6 gram, HPLC can detect the concentration of L-DOPA between 0.05 to 3 mg/L. However, characterization using electrophoresis gel was unsuccessful to determine the weight of protein in the samples.